PERBUATAN MELAWAN HUKUM AKIBAT PERALIHAN HAK MILIK TANAH DITINJAU DARI PASAL 1365 KUH PERDATA DAN PASAL 26 UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA DAN PP NO. 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH (Studi Kasus Putusan Pengadilan Negeri Jakarta Barat 252/Pdt.G/2018/Pn Jkt.Brt) - Norman Hamonangan; Yusman Yusman (Rechtsregel : Jurnal Ilmu Hukum, 2020)
Property rights to land are the strongest and fullest inherited rights that can be owned over land and Transfer of ownership rights to land is the transfer or transfer of ownership rights to a plot of land or several parcels of land from the original owner to the new owner due to something or certain legal actions. The legal act of transferring rights is aimed at transferring land rights to another party permanently (in this case the legal subject meets the requirements as the holder of land rights). Transfer of land rights can occur because of transfer or transfer. Switching, for example because of inheritance while it is transferred, for example on the basis of sale and purchase, exchange, grants, will grants and other legal acts of transfer of rights.